Contamination and isotopic composition of Pb and Sr in offshore surface sediments from Jiulong River, Southeast China. (November 2016) - Lin, Chengqi; Yu, Ruilian; Hu, Gongren; Yang, Qiuli; Wang, Xiaoming
Abstract: Concentrations and isotopic compositions of Pb and Sr in the surface sediment samples from Jiulong River, Southeast China, were determined to trace the sources of Pb and Sr. The average concentrations of Pb and Sr were 110.9 mg/kg and 69.2 mg/kg, approximately 3.2 and 2.0 times of the local soil background values, respectively. Average 62.9% of total Pb and 36.8% of total Sr in the investigated surface sediment samples were extracted by 0.5 mol/L HNO3 . Pb and Sr presented slight contamination, and Pb showed low ecological risk for most of surface sediment samples in Jiulong River according to geo-accumulation index ( I geo ) and potential ecological risk index (RI). The results of Pb isotopic compositions in sediment samples and potential sources showed that the Pb accumulated in the surface sediments of Jiulong River was mainly from parent material, coal combustion and Fujian Pb-Zn deposit, with the contribution rates of 34.4%, 34.0%, and 31.6%, respectively. The results of Pb isotopic compositions in 0.5 mol/L HNO3 -extraction suggested that dilute HNO3 -extraction was more sensitive in identifying anthropogenic Pb sources than total digestion. The results of Sr isotopic compositions showed that Sr accumulated in the surface sediments of Jiulong River estuary mainly derived from external source and natural source (parent material) with the contribution rates of 48.1% and 51.9%, respectively. Graphical abstract: Highlights: Pb and Sr in the surface sediments of Jiulong River, Southeast China were analyzed. Pb was mainly from parent material (34.4%), coal combustion (34.0%) and Pb-Zn deposit (31.6%). Sr was mainly from natural source (51.9%) and external source (48.1%). Dilute HNO3-extraction was more sensitive in identifying anthropogenic Pb sources. Combining Pb and Sr isotopes can identify pollution sources more accurately. Abstract : Pb was mainly from parent material (34.4%), coal combustion (34.0%) and Fujian Pb-Zn deposit (31.6%); Sr was mainly from natural source (51.9%) and external source (48.1%).